COMPARISON OF MECHANICAL BOWEL PREPARATION VERSUS REGULAR DIET BEFORE VAGINAL PROLAPSE SURGERY: A RANDOMIZED CONTROLLED TRIAL - Tayyab, Wajida; Hafeez, Humaira; Manzoor, Shahla; Hameed, Asma; Saifuddin, Zainab (Pakistan Armed Forces Medical Journal, 2019)
Objective:The objective of this study was to compare patient’s response rate with and without mechanical bowel preparation before vaginal prolapse surgery.Study Design: Randomized controlled trial.Place and Duration of Study: This study was carried out at the Department of OBGYN DHQ Teaching Hospital Rawalpindi from 7th Jan 2017 to 7th Jul 2017.Material and Methods:After approval from hospital ethical committee, a total of 60 patients fulfilling inclusion and exclusion criteria were taken. They were randomly divided into 2 equal groups using lottery method. In group-A the patients had Mechanical bowel preparation and in group-B patients had their regular diet before vaginal prolapse surgery (hysterectomy, anterior or posterior repair) and were just kept NPO from midnight. Results:Total 60 patients were randomly divided into two equal groups. Mean age (years) in the study was 52.78 ± 4.87. Patient response in terms of good response (absence of nausea, vomiting and anal irritation) with bowel preparation was 19 (63.3%) and without bowel preparation was 16 (53.3%). The patient response in terms of average response (having one symptom) with bowel preparation was 9 (30%) and without mechanical bowel prepration was 14 (46.7%). Only 2 patients (both in group A) had poor response (presence of 2 or more symptoms). This was statistically not significant (p-value 0.188).Conclusion:The study concluded that there was no difference in response with and without mechanical bowel preparation before vaginal prolapse surgery so there is no need of subjecting patients to bowel preparation before vaginal prolapse surgery.